2015
DOI: 10.1016/j.bbamem.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidative permeabilization of liposomes induced by cytochrome c/cardiolipin complex

Abstract: Interaction of cytochrome c with mitochondrial cardiolipin converting this electron transfer protein into peroxidase is accepted to play an essential role in apoptosis. Cytochrome c/cardiolipin peroxidase activity was found here to cause leakage of carboxyfluorescein, sulforhodamine B and 3-kDa (but not 10-kDa) fluorescent dextran from liposomes. A marked decrease in the amplitude of the autocorrelation function was detected with a fluorescence correlation spectroscopy setup upon incubation of dye-loaded cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…In several recent publications , the permeability of vesicle membranes to fluorescent dyes has been studied by fluorescence correlation spectroscopy (FCS). This approach does not require loading of liposomes with dyes at very high, self‐quenching concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several recent publications , the permeability of vesicle membranes to fluorescent dyes has been studied by fluorescence correlation spectroscopy (FCS). This approach does not require loading of liposomes with dyes at very high, self‐quenching concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…This approach does not require loading of liposomes with dyes at very high, self‐quenching concentrations. Previously, we have shown that the addition of Fe 2+ (5 μ m ) together with Asc (100 μ m ) brings about permeabilization of liposomes formed from the mixture of soybean phosphatidylcholine with bovine heart cardiolipin, as monitored by changes in the fluorescence intensity autocorrelation function ( G (τ)) of the water‐soluble dye sulforhodamine B (SRB) encapsulated in liposomes . Here, we studied the effect of the combination of Fe 2+ and Asc on G (τ) of SRB‐loaded liposomes prepared from lipid mixtures containing linoleoyl stearoyl phosphatidylcholine (H‐Lin‐PC) as the bulk lipid (unless otherwise stated) with various contents of a series of 1‐stearoyl phosphatidylcholines, bearing deuterated Lin, Lnn, Ara, EPA, or DHA fatty acids at position 2 of glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,7,8 Cyt c mediated oxidization of the hydrocarbon chains of CL generates an early signal in the intrinsic pathway of apoptosis, 8 and may contribute to mitochondrial membrane permeabilization. 9 The specificity of CL oxidation indicates the existence of a well-defined hydrocarbon binding site. 10,11 Despite considerable effort, an atomic resolution structure of the Cyt c hydrocarbon binding site has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we monitored the cyt c /H 2 O 2 ‐induced liposome leakage by an increase in the fluorescence of carboxyfluorescein. This dye, however, appeared itself to be a subject of peroxidative destruction by the cyt c /cardiolipin‐complex, which caused a decline of its fluorescence . Calcein was found to be much more stable than carboxyfluorescein (Data S1).…”
Section: Resultsmentioning
confidence: 99%
“…Cyt c/cardiolipin peroxidase activity has been previously found to cause permeabilization of liposome membranes [18,19], as evidenced by leakage from liposomes of fluorescent probes, such as carboxyfluorescein, sulforhodamine B, and 3-kDa (but not 10-kDa) fluorescent dextran [20]. The liposome leakage induced by horse heart cyt c in the presence of hydrogen peroxide has appeared to be sensitive to the inhibiting action of antioxidants, for example, trolox, butylated hydroxytoluene, and quercetin [20]. Here, we studied the effect of SkQ1 on the cyt c-induced peroxidative permeabilization of liposomes and the protein binding to membranes, which enabled us to gain insight into the mechanism of SkQ1 interference with cyt c/cardiolipin peroxidase activity.…”
Section: Abstract: Antioxidant; Binding; Cardiolipin; Cytochrome C; Lmentioning
confidence: 99%